1977
DOI: 10.1084/jem.145.6.1590
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of B-lymphocyte function. III. In vivo and in vitro studies on the ease of tolerance induction in B lymphocytes from fetal, neonatal, and adult mice

Abstract: It has generally been felt that tolerance can be induced more readily in neonatal than in adult animals. While this is clearly true in allograft tolerance induction (1), it has been less obvious with other antigens. Thus, Siskind et al.(2) and Howard and Hale (3) found no difference between neonatal and adult mice in regard to tolerance induction with polysaccharide antigens and Dresser (4) found that the dose of aggregate-free bovine gamma globulin (BGG) 1 required to induce tolerance in mice was the same in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Numerous reports have documented the extreme sensitivity of neonatal B cells to multivalent antigens compared with adult B cells (5,20,(26)(27)(28)(29)(30). Likewise, in this study it was found that neonatal unfractionated spleen cells and s-Ig-positive B cells were sensitive to tolerogen with an ~60-70% reduction in responsive B cells, although adult unfractionated spleen cells and adult s-Ig-positive B cells remained refractory to tolerogen.…”
Section: Discussionsupporting
confidence: 47%
“…Numerous reports have documented the extreme sensitivity of neonatal B cells to multivalent antigens compared with adult B cells (5,20,(26)(27)(28)(29)(30). Likewise, in this study it was found that neonatal unfractionated spleen cells and s-Ig-positive B cells were sensitive to tolerogen with an ~60-70% reduction in responsive B cells, although adult unfractionated spleen cells and adult s-Ig-positive B cells remained refractory to tolerogen.…”
Section: Discussionsupporting
confidence: 47%
“…The one major caveat in suggesting that the in vilro model reflects in vivo differentiation is the recent finding of Szewczuk & Siskind (1977). Hence, the issue raised by Szewczuk & Siskind (1977) is not yet resolved. They therefore questioned the physiological significance of in vitro models in which polyvalent antigens, such as heavily conjugated DNP-HgG are employed.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Thus, studies by Szewczuk & Siskind (1977) and by Howard & Hale (1976) indicate that adult and neonatal B cells responding to TI antigens are equally susceptible to tolerance induction. Thus, studies by Szewczuk & Siskind (1977) and by Howard & Hale (1976) indicate that adult and neonatal B cells responding to TI antigens are equally susceptible to tolerance induction.…”
Section: Tolerance Induction In B Cells Responding To Ti and Td Formsmentioning
confidence: 99%
“…The numbers of memory B cells (CD27+) are increased with aging [27]. An increased proportion of mature B cells may also account for the increased resistance to tolerance induction in the elderly [2831]. …”
Section: Changes Of the Immune System With Agingmentioning
confidence: 99%